Identifying Intrinsic and Extrinsic Motivations for Customer Participation in Value Co-Creation in the East Azerbaijan Province Footwear Industry - Rezabeigi , Saeed; Bafandeh, Alireza; Ali , Samad (Future of Work and Digital Management Journal, 2025)
Human beings, as complex entities with diverse motivations, are considered the most significant influencing factor in business. Undoubtedly, customers are regarded as valuable assets for organizations. The footwear industry, with its vast base of potential and actual customers, inevitably requires the identification of various customer motivations for participating in value co-creation. Two key challenges currently facing the footwear industry in the customer domain are: (1) What are the motivations driving customers to participate in value co-creation? and (2) How can these motivations be categorized into intrinsic and extrinsic types? Accordingly, footwear industry stakeholders can achieve greater sustainability in the market by considering these motivations. The footwear industry in East Azerbaijan Province, known as the footwear capital of Iran, serves as a comprehensive and representative example of the country’s footwear sector. Therefore, the overall aim of this study is to present a model of customer participation motivations in value co-creation within the footwear industry of East Azerbaijan Province. Given the stated issues, this study employed an applied-developmental approach using a mixed-method (qualitative–quantitative) design. In the qualitative section, the multi-grounded theory method—combining meta-synthesis and grounded theory—was utilized. First, the literature on customer participation in value co-creation from 2000 to 2024 was reviewed, and subsequently, interviews were conducted with 10 footwear industry experts. Data analysis was carried out using open, axial, and selective coding following the Anselm Strauss and Juliet Corbin approach. In the quantitative section, the validity of the model was confirmed through structural equation modeling. The motivations for customer participation in value co-creation in the footwear industry were divided into two categories: intrinsic and extrinsic motivations. All identified motivations were found to be significant at the 95% confidence level. Eight factors were identified as intrinsic motivations and fourteen factors as extrinsic motivations. Among them, cost management, individual characteristics, and customer knowledge were among the most important intrinsic motivations, while value chain management, performance-based management, and organizational communication were among the most important extrinsic motivations.